Penilaian Tingkat Kesehatan Bank DKI Mengunakan Risk Based Bank Rating Ratio - Aulia Yunicha Harly; Lizabeth Sari Dewi; Hasan Basri; Ratih Rosita (J-MAS (Jurnal Manajemen dan Sains), 2021)
As one of the intermediation institutions and also a source of regional income, regional development banks (BPD) are currently faced with increasingly fierce competition. This study is titled assessment of the health level of bank DKI using RBBR ratio (Risk Based Bank Ratting) with the main focus in this study is to know and analyze the health level of regional development banks by using rbbr ratio as an assessment tool. The research method used is quantitative analysis that uses secondary data sourced from the bank's annual report in the period 2016 to 2020. The results of the study showed that the health level of DKI bank based on the overall RBBR Ratio showed good health performance in this study period. In 2016 the health assessment was good, in 2017 in 2018 in 2019 and in 2020.